2006
DOI: 10.1007/s10725-006-9101-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt and drought stress on antioxidant enzymes activities and SOD isoenzymes of liquorice (Glycyrrhiza uralensis Fisch)

Abstract: The effects of salinity and drought on the antioxidative system (SOD, POD, CAT) were studied in liquorice seedlings (Glycyrrhiza uralensis Fisch). The results showed that both salt and drought stresses could induce oxidative stress, as indicated by the increase level of lipid peroxidation. The activities of SOD and POD were upregulated by salt and drought stress, while CAT activity decreased. An additional MnSOD isoenzyme was detected in liquorice subjected to 2%NaCl stress. The data also showed that although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
125
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(157 citation statements)
references
References 37 publications
26
125
2
4
Order By: Relevance
“…According to this fact that SOD processing is known to be substrateinducible (Tsang et al 1991), an increase in the SOD activity may be attributed to the increased production of active oxygen species as substrate that lead to increased expression of genes encoding SOD. Our results are consistent with other studies reporting the increased SOD activity in response to drought stress in sunflower (Gunes et al 2008), poplar (Xiao et al 2008), cowpea (Manivannan et al 2007), liquorice (Pan et al 2006), wheat (Bakalova et al 2004;Csiszar et al 2005) and pea (Malecka et al 2001).…”
Section: Discussionsupporting
confidence: 93%
“…According to this fact that SOD processing is known to be substrateinducible (Tsang et al 1991), an increase in the SOD activity may be attributed to the increased production of active oxygen species as substrate that lead to increased expression of genes encoding SOD. Our results are consistent with other studies reporting the increased SOD activity in response to drought stress in sunflower (Gunes et al 2008), poplar (Xiao et al 2008), cowpea (Manivannan et al 2007), liquorice (Pan et al 2006), wheat (Bakalova et al 2004;Csiszar et al 2005) and pea (Malecka et al 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Unlike POX, CAT levels continued to decline with increasing concentration of NaCl and extended time of exposure (Figure 3), suggesting the primacy of POX in H 2 O 2 detoxification. These observations in Niger are in good agreement with salt and drought stressed liquorice [44], heavy metal stressed sunflower [45] and salt stressed Jatropha curcas L. [46].…”
Section: Discussionsupporting
confidence: 82%
“…A. thaliana exposed to oxidative stress showed rise in the activity of CuZnSODs, however MnSOD isoforms showed no change (Kliebenstein et al 1998). In Glycyrrhiza uralensis, drought stress induced no change in MnSOD and FeSOD activities; however CuZnSOD showed most abundant activity (Pan et al 2006). Increase in the activity of CuZnSODs was also observed in rice and pea plants exposed to drought (Ke et al 2009;Moran et al 1994).…”
Section: Discussionmentioning
confidence: 88%
“…SODs are classified into FeSODs (Iron SODs), MnSODs (manganese SODs) and CuZnSODs (copper zinc SODs) based on the use of metal cofactor, with a critical role of CuZnSODs under oxidative stress (Mittler 2002;Sunkar et al 2006). The SOD isoenzymes identified in these two plant species were based on their differential sensitivity to KCN and H 2 O 2, which were comparable to the ones observed in Glycyrrhiza uralensis (Pan et al 2006). In the current study both the species showed rise in the activity of all SOD isoforms in response to water deficit, however it was comparatively higher in I. campanulata.…”
Section: Discussionmentioning
confidence: 96%